Cystoid macular oedema after descemet membrane endothelial keratoplasty. Issue 4 (8th November 2021) - Guindolet, Damien; Huynh, Odile; Martin, Gilles C; Disegni, Hugo; Azar, Georges; Cochereau, Isabelle; Gabison, Eric
Abstract : Aims: To determine the incidence and risk factors of cystoid macular oedema (CMO) following descemet membrane endothelial keratoplasty (DMEK) with or without combined cataract surgery (triple-DMEK). Methods: We reviewed the records of patients who underwent DMEK surgery alone or triple-DMEK performed at the Rothschild Foundation Hospital (Paris, France) between January 2019 and March 2020. Patients with pre-existing CMO observed on the preoperative macular optical coherence tomography (OCT) were excluded. Spectral-domain OCT was performed in patients with postoperative visual impairment. Data regarding comorbidities, intraoperative characteristics and postoperative treatments or complications were collected and analysed. Univariate and multivariate analyses were performed. Results: Twenty three of 246 eyes (9.36%) developed clinically significant (cs)-CMO after DMEK. Triple-DMEK was not associated with a higher risk to develop CMO (12.2% in DMEK alone and 6.1% in triple-DMEK). Pseudophakic bullous keratopathy (PBK ; 39.1% vs 9%; OR=3.5 (1.0 to 11.8), p=0.045) and epiretinal membrane (ERM; 39.1% vs 7.7%; OR=10.5 (3.4 to 32.3), p<0.001) were more frequently observed in patients who developed CMO. The occurrence of hyphaema during surgery was statistically associated with postoperative CMO (13% vs 1.3%; OR=7.1 (1.0 to 48.8) p=0.045). Peroperative epithelial debridement was statistically associated with postoperative CMO (65.2% vs 33.2%, p=0.005), but only in univariate analysis. Conclusions: We identified a clinically significant CMO incidence of 9.35% after DMEK. Patients with a history of ERM, PBK and intraoperative hyphaema may be at risk of developing CMO after DMEK surgery and should be monitored.